2013
DOI: 10.1152/ajpregu.00005.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acute on chronic exposure to endotoxin is associated with enhanced chemoreflex responses in preterm fetal sheep

Abstract: Acute on chronic exposure to endotoxin is associated with enhanced chemoreflex responses in preterm fetal sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…; Booth et al . ). As seen in neonatal models, in the sheep fetus the fetal adaptive responses to asphyxia are also influenced by the timing between the exposure to LPS and asphyxia, albeit very few antenatal studies have been performed.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Booth et al . ). As seen in neonatal models, in the sheep fetus the fetal adaptive responses to asphyxia are also influenced by the timing between the exposure to LPS and asphyxia, albeit very few antenatal studies have been performed.…”
Section: Introductionmentioning
confidence: 97%
“…) (Booth et al . ). Faster and more sustained peripheral vasoconstriction ensured blood pressure was higher, offsetting the lower FHR induced by LPS, and perfusion was better as fetuses entered phase three (Fig.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have recently reported that in preterm fetal sheep 48 hours exposure to a low-dose chronic infusion of LPS, that did not cause any hemodynamic disturbance, before three boluses of high-dose LPS 24 hours apart significantly reduced mortality and attenuated the nadir of hypotension after the LPS boluses [17,18]. This paradigm of acute-on-chronic LPS was associated with a fetal inflammatory response and white matter injury.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the evidence discussed above that a four-hour delay after acute LPS exposure typically increases HI injury in neonatal animals [12], asphyxia was induced four hours after the last bolus of high-dose LPS. We have previously shown that a similar paradigm of acute-on-chronic LPS exposure was associated with more rapid chemoreflex adaptation to umbilical cord occlusion and did not compromise fetal hemodynamic adaptation [18]. The neural maturation of 0.7 ga fetal sheep is broadly equivalent to between 28 and 32 weeks of human development [20].…”
Section: Introductionmentioning
confidence: 99%